Legal Awareness And Student Bullying Behavior In The Digital Age - Susi Susi; Sunarso Sunarso; Suharno Suharno; Suwandi Suwandi; Sri Rahayu Pudjiastuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Bullying among students has become an increasingly complex educational problem in the digital age, as aggressive behavior is no longer limited to direct physical or verbal interaction but also occurs through online platforms. This study aims to examine the influence of legal awareness and the social/digital environment on students’ bullying behavior. A quantitative approach with a survey design was employed. The participants consisted of 30 senior high school and vocational high school students in Pamulang District, selected through random sampling. Data were collected using a Likert-scale questionnaire measuring three variables: legal awareness, social/digital environment, and bullying behavior. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with the assistance of IBM SPSS Statistics. The findings reveal that legal awareness has a significant effect on students’ bullying behavior, with a regression coefficient of 0.754 and a significance value of 0.000. In contrast, the social/digital environment does not have a significant partial effect, with a significance value of 0.434. Simultaneously, legal awareness and the social/digital environment significantly influence bullying behavior, as indicated by an F-value of 613.115 and a significance value of 0.000. The coefficient of determination shows an R Square value of 0.978, meaning that 97.8% of the variance in bullying behavior can be explained by the two independent variables. These findings imply that strengthening students’ legal awareness through civic education, legal literacy, digital ethics, and character education is essential for preventing bullying in schools. The study contributes to the development of school-based anti-bullying strategies by emphasizing the internalization of legal values, social responsibility, and ethical digital citizenship among students.